Development and characterization of microsatellite loci in the marsh deer (Blastocerus dichotomus Cervidae) - Francisco Oliveira, Eddy Jose; Garcia, José Fernando [UNESP]; Barbanti Duarte, Jose Mauricio [UNESP]; Betioli Contel, Eucleia Primo (Springer, 2009)
Marsh deer (Blastocerus dichotomus) is one of the most exposed large mammals in South America. To aid in the conservation management of the species, nine polymorphic microsatellite loci were isolated and tested on up to 50 animals, showing 3-12 alleles and expected heterozygosity values varying from 0.69 to 0.89. These markers should be of considerable utility in future population and ecological genetics studies of this species. The marsh deer (Blastocerus dichotomus) is the biggest South American species of deer. Originally distributed across a large part of South America, stretching from the south bank of the Amazon river to northern Argentina, significant wild populations are now restricted to the Pantanal, swamplands that cover about 40% of southwest Brazil. The marsh deer is listed as Vulnerable on the Red List of the IUCN. Three populations of the species from three areas in the Parana River basin (between the states of São Paulo and Mato Grosso do Sul) were recently studied by observing protein polymorphism at 17 loci (Oliveira et al. 2005). Now we are presenting data about isolation of microsatellite markers to improve the results regarding population structure.
Keywords: Marsh deer; Blastocerus dichotomus; Cervidae; Microsatellites; Enriched library